Penggunaan Flash Card sebagai Media Pembelajaran Interaktif untuk Meningkatkan Penguasaan Materi Tarkib Bahasa Arab - Hermansyah, Yudisthira Ade (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2025)
In the 5.0 era, language has become a highly urgent matter, and Arabic is one of the languages used by people around the world. One of the main reasons students struggle to learn Arabic today is the lack of use of instructional media that can help them understand the material more easily and enjoyably. In fact, the use of media in learning greatly supports the effective implementation of the teaching and learning process. Flash cards are considered one of the effective instructional media in helping students understand Tarkib material, as they allow students to construct and interpret vocabulary independently. This enables students to learn independently and think more critically. This study aims to determine whether flash cards have a significant effect on learning outcomes in the Arabic Tarkib subject at SMK Muhammadiyah 5 Kepanjen. As part of an experimental approach, this study involves the use of pre-test and post-test to measure changes in learning outcomes. The research data were analyzed using SPSS version 26.0 for Windows. Based on the t-test results, the significance values (Sig. 2-tailed) were 0.038 for post-test data and 0.026 for gain score data. Since both values are less than 0.05, H₀ is rejected and Hₐ is accepted. This indicates that the use of flash card instructional media has a significant effect on the learning outcomes of Arabic Tarkib material.